Changes in Global Longitudinal Strain after TAVI : Additional Prognostic Value over Cardiac Damage in Patients with Severe Aortic Stenosis - Myagmardorj, Rinchyenkhand; Fortuni, Federico; Galloo, Xavier; Nabeta, Takeru; Meucci, Maria C.; Butcher, Steele C.; van der Kley; Frank; Bax, Jeroen J.; Ajmone Marsan, Nina (MPDI, 2025)
Background:
Previous studies demonstrated the prognostic value of baseline cardiac damage staging as well as left ventricular global longitudinal strain (LVGLS) in patients undergoing transcatheter aortic valve implantation (TAVI). The aim of the present study was to evaluate the changes in cardiac damage stage and LVGLS after TAVI and to investigate their prognostic values when integrated into the follow-up assessment.
Methods:
Patients with severe aortic stenosis undergoing TAVI were hierarchically classified into cardiac damage stages based on echocardiographic criteria before TAVI and at a 6-month follow-up. At the same time, LVGLS was measured. The staging system included stage 0 = no signs of cardiac damage; stage 1 = LV damage; stage 2 = mitral or left atrial damage; stage 3 = pulmonary vasculature or tricuspid damage; and stage 4 = right ventricular damage. The primary endpoint was all-cause mortality.
Results:
A total of 620 patients were included. At follow-up, LVGLS significantly improved, and the improvement was similar among each baseline cardiac damage stage. Follow-up LVGLS values were divided into quintiles, and each quintile was integrated into the cardiac damage staging, leading to a reclassification of 308 (50%) patients. At the time of a median follow-up at 48 (IQR 31-71) months starting from the 6-month follow-up after TAVI, 262 (38%) patients had died. A multivariable Cox regression model showed that LVGLS-integrated cardiac damage staging at follow-up had an incremental prognostic value over the baseline assessment (HR per 1-stage increase 1.384; 95% CI 1.152-1.663; p < 0.001).
Conclusions:
The integration of LVGLS with conventional echocardiographic parameters of cardiac damage at a 6-month follow-up after TAVI can improve patient risk-stratification.